THE ROLE OF STRATEGIC LEADERSHIP IN CRISIS MANAGEMENT AN APPLIED STUDY OF A SAMPLE OF TRAINERS IN THE DIRECTORATE OF EDUCATION OF DHI QAR - Zainab Hadeed Hamza; Azhar Abed Mohisen Alrikabi; Khalid Jameel Kamil; Krar Mohsin Thajil; Ali Salah Hasan; Saadulldeen Ali Hussein (Journal Park Publishing, 2023)
This research aims to identify the mechanisms and practices of strategic leadership and its role in crisis management in government institutions in Iraq. So, the existence of a strategic leadership that is one of the most important constituents of the organizations in the course of development, which allows them to face the various problems, unrest and crises that may be exposed to them, and in light of the circumstances that Iraq is going through, the presence of such strategic leaders signs that it has a prominent role in facing the crises that Government institutions are exposed to it at the present time. The conceptual framework for the current study is built on these two main variables. This study was applied in the government education sector in Iraq. A questionnaire will be developed to make sure that there is a relationship between the main variables of the study (strategic leadership, crisis management) as a tool for collecting data in eight sections of the General Education Directorate in Dhi Qar for a sample (201) of the directors in the Directorate of Education and its departments, who were chosen randomly and using a group One of the statistical tools included in the programs (SPSS. V.22 - AMOS V.22).
Keywords: strategic leadership, government institutions, crisis management.